2018
DOI: 10.1109/trpms.2017.2771490
|View full text |Cite
|
Sign up to set email alerts
|

MR-Guided Kernel EM Reconstruction for Reduced Dose PET Imaging

Abstract: Abstract-PET image reconstruction is highly susceptible to the impact of Poisson noise, and if shorter acquisition times or reduced injected doses are used, the noisy PET data become even more limiting. The recent development of kernel expectation maximisation (KEM) is a simple way to reduce noise in PET images, and we show in this work that impressive dose reduction can be achieved when the kernel method is used with MR-derived kernels. The kernel method is shown to surpass maximum likelihood expectation maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…Therefore, in relatively uniform MR regions where the MR intensity values are similar, spatially close voxels will be selected over more disparate voxels, thereby helping recovery of PET-unique features. More generally, KEM has been applied to a range of reconstruction problems, [12][13][14][15][16][17][18][19][20][21] and is an example of a broader cohort of algorithms that reparameterize the emission image into an alternative set of basis functions. [22][23][24] In contrast to reparameterizing the reconstruction process, MR information can alternatively be included into the reconstruction process through the addition of a regularizing term in either a Bayesian maximum a posteriori (MAP) or penalized maximum likelihood (PL) framework.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in relatively uniform MR regions where the MR intensity values are similar, spatially close voxels will be selected over more disparate voxels, thereby helping recovery of PET-unique features. More generally, KEM has been applied to a range of reconstruction problems, [12][13][14][15][16][17][18][19][20][21] and is an example of a broader cohort of algorithms that reparameterize the emission image into an alternative set of basis functions. [22][23][24] In contrast to reparameterizing the reconstruction process, MR information can alternatively be included into the reconstruction process through the addition of a regularizing term in either a Bayesian maximum a posteriori (MAP) or penalized maximum likelihood (PL) framework.…”
Section: Introductionmentioning
confidence: 99%
“…The recently proposed hybrid kernel expectation maximization (HKEM) method [14], [15], which uses information from both PET and an anatomical image in order to compensate for partial volume effects, was used in this study. The advantage of the kernel method is that it does not require segmentation and it achieves improved resolution for each individual voxel and also for the edges of a region [16], [17]. This technique, although it is not a dedicated partial volume correction technique, was used so as to explore the edge-preserving and noise-suppression performance in enhancing resolution recovery and reducing the spill-in effect from the hot background into the colder ROIs [18].…”
Section: Hybrid Kernel Expectation Maximization (Hkem)mentioning
confidence: 99%
“…Gong et al [7] used a hybrid kernel method to perform direct Patlak reconstruction from dynamic PET using MR and PET information where the latter was obtained by combining different frames. Bland et al (2017) [28] studied the effect of KEM on simulated dose-reduced datasets, showing improved contrast to noise ratio, but at the cost of possible over-smoothing of features unique to the PET data. To overcome this issue [29] proposed a method using a spatially constrained MR kernel in order to maintain the noise reduction properties of the conventional kernel method, whilst better retaining the features unique to the PET data.…”
Section: Introductionmentioning
confidence: 99%
“…This is important because in some cases a PET lesion may be detected at the border between two different regions, as shown in [24]. Moreover, it has been shown that PET unique features can be severely over-smoothed [28] with the MR-guided kernel. Strul and Bendriem [33] investigated the limitations, due to MR segmentation and PET-MR registration, of different segmentation-based partial volume correction techniques.…”
Section: Introductionmentioning
confidence: 99%